CONCEPTUAL PRINCIPLES OF CLASSIFICATION OF INDICATORS FOR RISK ASSESSMENT IN THE NATIONAL ECONOMY FUNCTIONING - KAMINSKYI, Andrii; CHYNCHYK, Anatolii; HOLUBKA, Stepan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Based on a comprehensive theoretical analysis of prevailing approaches to the study and structuring of classification systems, this paper proposes a novel methodology for the systematic grouping and evaluation of indicators related to the risk of committing criminal offenses in the economic sector. The proposed classification framework centers on three core dimensions: the nature and magnitude of the threat, the vulnerability of institutions and systems to such threats, and the socio-economic consequences arising from potential or actualized threats. This tripartite structure provides a holistic foundation for risk identification and assessment within the national economy. The study delineates distinct categories of performance indicators and consequential metrics to evaluate institutional capacity, with particular attention to how the expert community perceives the threat levels associated with relevant state institutions. These indicators serve to benchmark the efficiency and reliability of governmental bodies in executing their mandated functions. Special emphasis is placed on the evaluation of vulnerabilities as a critical element in the proactive management of risks. This includes the early identification, detection, and rapid mitigation of threats that could compromise the economic security of the state. Vulnerabilities, in this context, are interpreted as both structural and procedural weaknesses that may be exploited in criminal activity. Furthermore, performance indicators are not only utilized for performance appraisal but also serve as diagnostic tools for uncovering risk-prone institutional areas caused by low-functioning capacities. Consequential indicators, on the other hand, are pivotal in aligning qualitative insights with quantitative assessments to provide a comprehensive view of threat intensity and potential impact. Overall, the study substantiates the theoretical and practical value of using structured, multidimensional indicators for the accurate assessment of economic crime risk levels and offers a robust framework for enhancing institutional resilience and national economic security.